A chemical investigation of Cassia alata L. (Fam. Leguminosae) - Villarroya, Maria Luisa E.
Compounds I to VI were isolated from Cassia alata L. by column chromatography. Compounds I to IV were found to be chrysophanol, emodin, rhein and aloe-emodin, respectively by TLC, melting point determinations, UV and IR spectral analyses. Compound V was found by TLC using a different solvent system to be a mixture. Compound VI, C35 H58 O6, m.p. 277-8 (CHCl3-MeOH) and with an acetate derivative melting at 164-5(degrees), was identified as a sitosterol glycoside with two conjugated double bonds in the tetracyclic moiety by UV, IR, NMR and mass spectral analyses.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1975.
Keywords: Plants -- Analysis